THE DINAMICS OF THE FORMAL LABOR MARKET OF THE SUGAR AND ALCOHOL INDUSTRY OF PARANÁ FROM 2000 TO 2017: EMPLOYMENT EVOLUTION AND PROFILE OF WORKER (Desenvolvimento em Questão, 2020)
This paper analyzes the dynamics of the formal labor market of the sugar and alcohol industry of Paraná from 2000 to 2017, considering the jobs’ creations and the profile of workers, based on the Annual List of Social Information (RAIS) and the General Register of Employed and Unemployed Persons (CAGED). The workers were classified intrasetorially, through their activity, by using the Brazilian Classification of Occupations (CBO) categories to highlight the agricultural workers of the others. The data shows to a significant increase in the number of jobs between 2000 and 2009, especially those related to agricultural activities, in addition to a continuous decline after 2009, with a particular highlight of farming activities. In this last period there were significant changes in the profile of the worker: older; better-educated and better-paid.
Keywords: Jobs. Sugar. Alcohol. Paraná.